Psychological and Social Problems of the Elderly:: A Field Study at the Retirement Home in the Wilaya of Oum El-Bouaghi - Ameur, Nora (Journal of Human Sciences, 2022)
The Elderly people living in the retirement homes represent a very fragile social category. They used to live with their families and now they find themselves in a different place, served by strangers, and must respect the rules of this place. Consequently, they suffer from social and psychological problems. So, this study aims to discuss the impact of the retirement homes on the elderly people and observe the social and psychological problems they face. This research relies on the descriptive analytical approach and employs an interview with a group of elders who stay at the retirement home in the city of Oum El-Bouaghi. This group consists of 19 persons- aged 65 and above. The study finds that there are social and psychological problems such as alienation, isolation, depression, and difficulty to cope with the environment.